KEARIFAN LOKAL DALAM BUDAYA PEKANDANGAN DI KABUPATEN KUANTAN SINGINGI - Zulfan Saam; Raja Arlizon (Program Pascasarjana Universitas Riau, 2011)
A qualitative research was conducted to analyze values of local wisdom of Pekandanganculture in Kuantan Singingi Regency. This study is a qualitative research. Data are collectedthrough observation, documentation, and dept interview with the key informans including thechief Pekandangan Kerbau and society leader. The result of this study shows the following :The culture Pekandangan Kerbau contains the values local traditions or local wisdom are : (1)there are mudhole in perkandangan area (2) insect bite protection (3) there are protector treesin perkandangan area, (4) as the use of half dried log (mati koro), (5) the use of hard wood,buffaloes’ dirt for firewood; (6) the knowledge of hungry buffalo, (7) the consumtion of thehealth traditional food and (8) Mandawai is community working together (gotong royong). Thelocal wisdom is useful for the environment base development